Integrated model for reverse logistics management of electronic products and components - Dos Santos, Reinaldo Fagundes [UNESP]; Marins, Fernando Augusto Silva [UNESP] (Elsevier, 2015)
In August 2010, it was sanctioned a National Solid Waste Policy (PNRS - Política Nacional de Resíduos Sólidos) that features innovations as the Reverse Logistics which determines that manufacturers, importers, distributors and retailers must perform the collection of used packaging. Thus, what is the actual difficulty of companies in meeting the requirements of the PNRS? The purpose of this article is to propose a management model that uses Information and Communication Technology (ICT) and the WEB to assist in the integration of all stages of Supply Chains of electronic products and their components. It is an applied research with a qualitative approach where, after a critical analysis of the PNRS, a literature review was conducted involving the state of the art in Supply Chain Management, the ICT and the development of Enterprise Resource Planning (ERP) systems. The application of the proposed model in supply chains of electronic appliances through environmental protection and a direct interaction with the ultimate consumer offers enterprises a competitive advantage and can minimize financial losses associated with fines and violations. The following stages of this research include the development of a WEB portal with the proposed model and its availability for government use, thus enabling its practical application trials.
Keywords: 3rd generation erp; Information and comunication technology; Integrated management model; PNRS; Reverse logistics